Pengembangan Sistem Informasi Kesehatan Berbasis Web Berdasarkan Model Organisasi Dan Manajemen Kesehatan Primer "ANDAL" - Tri Wahyu Herlambang; Ismiarta Aknuranda; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The team of Public Health Sciences Faculty of Medicine Universitas Brawijaya (IKESMAS FKUB) initiated a strategic management model on primary health services with integrative, strategic, effective, efficient, quality, affordable and equitable management in the management of primary health care in a region called management model "Reliable". However, the implementation of this management model requires information systems that have certain characteristics that support the management model to make it faster and easier to collect and process data into information that can be utilized by stakeholders to improve primary health care. This study aims to build information systems to demonstrate the ability of the model of management reliably more easily and can be a pilot study to be applied in all primary health services so as to save health claims from participants BPJS Health. The results of this study are the development of web-based health information system through the process of requirements analysis, design, implementation, and testing. Testing conducted using Validation Testing method, Compatibility Testing, Condition Testing, Equivalence Partitioning, Boundary Value Analysis Shows the result that Information System built in this research can run well.